The search for truth and the system of proof in criminal proceedings (Revista do Tribunal Regional Federal da 3ª Região, 2021)
This article focuses on the understanding of truth in the context of criminal procedure, formulating objections and pointing out the contributions of each of the theoretical strands, with the aim of establishing a teleological framework for the issue under debate. In order to ensure coherence in the final conclusion, this study ends its program by addressing the constitutional models of the State and the legal nature of criminal procedure, as well as conceptual and developmental considerations about procedural systems. Finally, a favorable scenario has been formed so that the nuances of each of the theoretical proposals that build up the contextualization of the management of evidence can be examined, assessing the (in)adequacy of the ambition to search for a so-called truth.
Keywords: Democratic Rule of Law; the legal nature of criminal procedure; procedural systems; truth; management of evidence; the magistrate's instructional initiative